THE INFLUENCE OF SOWING METHODS, SEEDING RATES AND STANDING DENSITY ON THE GROWTH AND DEVELOPMENT OF THE SOYBEAN PLANT - Yormatova, D.; Abdinazarov, S.; Khamroyeva , M.; Khamroyev, O.; Yorov , K.; Baratov, J. (The journal of contemporary issues in business and government, 2022)
This article describes the sowing rate of soybean varieties in a hot, dry continental climate.The growth and development of soybean varieties, the formation of lateral branches, the number of beans, and the height of attachment of the lower beans were studied. It is determined that with an increase in the seeding rate and the density of standing, the yield of soybean seeds per hectare increases, only the weight of seeds of one plant decreases. An increase in the seeding rate to 500 thousand hectares leads to an increase in yield, a decrease in the density of standing leads to a decrease in yield.